Interaction of Type 1 Porcine Reproductive and Respiratory Syndrome Virus With In Vitro Derived Conventional Dendritic Cells - Li, Yanli; Mateu, Enric (Frontiers in Immunology, 2021)
The present study delineates the interaction of a typical PRRSV1.1 isolate 3267 with in vitro derived pig conventional dendritic cells, cDC1, cDC2, and a CD14+ population (CD14+ DCs). Only a fraction of CD14+ DCs were infected. After exposure to viral suspensions, all three DC types remained immature as determined by no increase of maturation molecules, no release of cytokines, no modification of antigen presentation abilities, and no alteration of endocytic/phagocytic capabilities. However, when the infected MARC-145 cells were used as a source of viral antigens, cDC2 and CD14+ DCs showed a significant increase in the expression of maturation molecules and released a significant amount of cytokines. To further address the impact of PRRSV1 3267 on TLR3- and TLR7-mediated activation, cDC1, cDC2, and CD14+ DCs were inoculated by the virus for 6 h prior to or simultaneously with the addition of poly I:C (TLR3 ligand) or gardiquimod (TLR7 ligand). Compared with TLR ligand alone, combination with the virus did not result in alteration to the maturation markers on all DC types but changed the cytokine response. Pre-exposure of cDC2 and CD14+ DCs to the live virus resulted in an increased the production IFN-α upon poly I:C stimulation, while pre-exposure to UV-inactivated virus enhanced the release of IL-10 upon gardiquimod stimulation. Simultaneous addition of the live virus and the TLR ligand either had no effect (mainly in cDC2) or impaired most of the cytokines after gardiquimod stimulation (in CD14+ DCs). When used as antigen presenting cells, cDC2 pre-inoculated by the live virus before addition of gardiquimod resulted in impaired proliferation of CD4–CD8¬– T cells. In the case of CD14+ DCs, pre-exposure to the live virus or simultaneously with the TLR ligand largely decreased the proliferation of CD4–CD8+ and CD4–CD8+ T-cell subsets. For cDC1, no significant changes were observed in cytokine responses or T-cell proliferation after poly I:C stimulation. Overall, these results suggest that exposure to PRRSV1 appears not to induce maturation of cDC1, cDC2, or CD14+ DCs, but might modify TLR3 and TLR7-associated responses (except for cDC1), which may affect the development of adaptive immunity during PRRSV1 infection.